Effects of Modified Constraint-Induced Movement Therapy in Real-World Arm Use in Young Children with Unilateral Cerebral Palsy: A Single-Blind Randomized Trial - Hwang, Young Sub; Kwon, Jeong-Yi (Neuropediatrics, 2020)
Objective To determine whether modified constraint-induced movement therapy (mCIMT) with continuous restraint is feasible and effective in improving the use of the paretic arm in the real world among infants and toddlers with unilateral cerebral palsy (CP).Design Single-blind randomized controlled trial.Setting Tertiary hospital.Participants Children aged 7 to 36 months with unilateral CP (N = 24; 16 boys, 8 girls).Intervention The experimental group received 2-hour clinic-based mCIMT sessions (5 days per week for 3 weeks), and a continuous restraint was applied.Main Outcome Measures Standardized assessments were conducted. Peabody Developmental Motor Scales-2 (PDMS-2), Gross Motor Function Measure-66, Pediatric Motor Activity Log (PMAL), and Pediatric Evaluation of Disability Inventory were measured pre- and postintervention. Children who agreed to participate in the accelerometer study additionally wore accelerometers on both their wrists for 3 days before and after the intervention.Results The mCIMT group exhibited greater improvement in PMAL-how often (p = 0.048; ηp2 = 0.173), PMAL-how well (p = 0.008; ηp2 = 0.289), and PDMS-2 visual motor integration (p = 0.014; ηp2 = 0.256) posttreatment than the control group. The percentage of time in moderate-to-vigorous physical activity (z = –2.24; p = 0.03) and vector magnitude average counts (z = –2.52; p = 0.01) significantly increased in children in who wore accelerometers (N = 8) after the 3-week mCIMT protocol.Conclusion mCIMT with continuous restraint applied to infants and toddlers with unilateral CP appeared to have a positive effect on paretic hand use in the real world.Clinical Trial Registration Number NCT03418519
Keywords: constraint-induced movement therapy; unilateral cerebral palsy; accelerometer; infants; toddlers